Percutaneous needle biopsy of the lung. Issue 6267 (14th March 1981) - Allison, D J; Hemingway, A P
Abstract : A total of 160 percutaneous needle biopsies of pulmonary lesions were performed in 149 patients. Cytological and bacteriological examination of the biopsy material yielded clinically useful information in 87% of these patients. False-negative diagnoses were made in 6%, but there were no false-positive diagnoses. In most patients the biopsy obviated the need for a diagnostic thoracotomy. The principal complication of the procedure was pneumothorax, which occurred in 24% of patients; the pneumothorax, however, was usually very small and only two of these patients required treatment with a pleural drain. There were no deaths in the series. It is concluded that percutaneous needle biopsy is an effective and relatively safe method of obtaining diagnostic material from a pulmonary lesion.